The Role of Product Localization in Guest Satisfaction : A Study of Quick Service Restaurants in Europe & the Middle East - Janoušek, Tadeáš; Pospíšil, Jan, 1983-; Tripes, Stanislav; Vysoká škola ekonomická v Praze. Fakulta managementu (2025)
This study explores the impact of menu localization on guest satisfaction in McDonald's and Burger King across Europe and the Middle East. Using Google Reviews as a measure, it analyzes whether higher localization scores correlate with customer ratings. Findings suggest that Burger King benefits from localization, especially in heavily lo-calized markets like Saudi Arabia and Portugal, while McDonald's sat-isfaction remains stable, indicating that brand consistency may be a stronger factor. This research provides practical insights for QSR brands on optimizing localization vs. globalization of menu items to enhance guest experience.
Vedoucí práce: Jan Pospíšil
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor bakal. práce]; bakalářské práce; bachelor's theses